The woman who can't forget : the extraordinary story of living with the most remarkable memory known to science : a memoir - Price, Jill, 1965-; Davis, Bart, 1950- (New York : Free Press, 2008)
This book presents the astonishing first-person account of living with the only diagnosed case of a remarkable superior memory condition, whereby the author remembers all the days of her life since age 14 in astonishing and unstoppable detail.
Alone with my memory -- The gift of forgetting -- When I was a child -- The remains of the days -- The stuff our selves are made of -- An archeology of time -- Speaking memories -- A window opens -- Beginning again -- The memory as memorial.
Includes bibliographical references (p. 253-260).
Keywords: Price, Jill, -- 1965-; Long-term memory -- Biography; Memory disorders -- Patients -- California -- Biography; Memoirs